Overview of Antibiotic Sensitivity Patterns in Diabetic Ulcers at Gatot Soebroto Army Hospital and Fatmawati General Hospital and The Review According to Islamic Perspective - Sherly Idhalhijah; Fatimah Eliana; Andri Gunawan (Junior Medical Journal, 2023)
Backgorund : One of the complications of DM is diabetic ulcers which occur due to reduced pain sensation due to neuropathy. Diabetic ulcers are a state of finding infection, destruction to the deepest skin tissue in the feet in patients with diabetes mellitus (DM) due to nerve abnormalities and peripheral arterial vascular disorders, so an overview of the pattern of antibiotics is very important in overcoming the severity of ulcers that can expand.Methodolgy : This research used secondary data from medical records on the antibiotic sensitivity of diabetic foot ulcer patients at the Gatot Subroto Army Hospital and Fatmawati General Hospital from January 2018 to December 2021.Results : There are ten types of antibiotics that sensitive to diabetic foot ulcer patients at Gatot Soebroto Army Hospital, including tigecycline, cefepime, piperacillin tazobactam, amikacin, aztreonam, ceftazidime, ciprofloxacin, gentamicin, meropenem, and ceftriaxone. While the types of antibiotics at Fatmawati General Hospital, include amikacin, piperacillin tazobactam, imipenem, meropenem, ertapenem, gentamicin, trimethophrim sulfamethoxazole, tigecycline, fosfomycin, and cefepime.Conclusion : Sensitive antibiotics in the two hospitals include tigecycline, cefepime, piperacillin tazobactam, amikacin, gentamicin and meropenem. In the view of Islam treatment is a form of effort to seek healing, after which surrender everything to Allah SWT.Keywords : Antibiotic, diabetic ulcer, Army hospital, Fatmawati